Unnoticed Gynaeatresia Leading to Recto-Vaginal Fistula from Coital Tear: A Rare Cause of Infertility: A Case Report from Sunyani Teaching Hospital in the Bono Region of Ghana in the Sub-Saharan Africa - Kwadwo, Addai-Darko; Bernard, Okyere; Elisha, Awuah; Banabas, Kpankyaano; Anto, Charles Osei; Dustine, Clarke Snr; Wunmi, Zakari-Saa; Boampong, Edmund; Kyeremeh, Isaac Opoku; Maximillian, Dono Kolbe; Alexander, Egote Kofi; Bosoma, Nana Emmanuel (Archives of Business Research, 2025)
Gynaeatresia, particularly of the acquired type, is a rare condition that may go unnoticed until it causes complications such as infertility. Even more uncommon is its association with recto-vaginal fistulae resulting from coital trauma. We report a case of a young woman with acquired partial vaginal atresia involving the outer third of the vagina. Over the years of marriage, she and her partner had unknowingly engaged in rectal intercourse due to the narrowed vaginal introitus. This resulted in an undiagnosed recto-vaginal fistula caused by coital trauma. The fistula subsequently became the default passage for coitus, with regular semen deposition into the rectum. The couple remained unaware of the anatomical abnormality for years, assuming normal sexual relations and attributing their infertility to natural delays. The condition was only revealed when the woman, prompted by the use of a newly installed water closet at home, sat in front of a mirror and noticed abnormal anatomical features. Further history revealed excessive vaginal douching eight years before marriage, likely resulting in scarring and subsequent gynaeatresia. The patient underwent a planned two-stage surgical intervention. First, the rectovaginal fistula was repaired to restore the anatomical barrier between the vagina and the rectum and to establish a sterile field. She was advised to abstain from sexual intercourse during the healing period. A definitive surgical correction of the vaginal atresia was scheduled for 1 month later, following adequate tissue healing. This case highlights a rare but significant cause of infertility resulting from acquired gynaeatresia and recto-vaginal fistula following coital trauma. It underscores the importance of thorough gynaecologic examination in cases of unexplained infertility, as well as public education on safe reproductive health practices. A staged surgical approach is crucial for optimal outcomes in managing coexisting rectovaginal fistula and acquired gynaeatresia.